Human resource management for organisational change theoretical formulations - Mishra, Paritosh 1962- (Routledge, 2022)
Change can take place in various forms, gradual or abrupt, incremental or transformational. It is a requirement in modern day society that everyone, whether at individual or organisational level, understands the softer nuances of this concept and prepares for it. During scenarios of change interventions, the role of human resources (HR) becomes highly crucial, even as the perception towards it becomes ambivalent. This volume delivers a holistic view on the role of HR in organisational change. It is built on the various theoretical models of change and provides a dramatic sequence of issues in change management to gain a big picture thinking for HR managers and weaves through why, how and what perspectives to change management. Human Resources Management for Organisational Change offers a comprehensive coverage of the changing role of HR as it relates to organisational change theories and models, strategy, changing business environment and implications, organisational culture, marc:leadership, resistance management, and high performance work practices (HPWP) to support change management and cost of no-changers. It is unique in that it covers the entire gamut of organisational change as well as HR. It will be of value to researchers, academics, professionals, and students interested in learning more about how organisational change can improve productivity and human satisfaction as well as the systematic approach to managing organisational change
Keywords: Organisationswandel; Personalpolitik